The Cave of Treasures on Swearing by Abel's Blood and Expulsion from Paradise: Two Exceptional Motifs in Context - Ruzer, Serge (Journal of early Christian studies, 2001)
In this essay, the version found in The Cave of Treasures (CT) of the expulsion from Eden and the story of Cain and Abel is analyzed. A peculiar combination of two exegetical motifs, discerned in this Syriac composition, is outlined: the canceling of the immediate effects of Adam's fall and the introduction of the salvific swearing by Abel's blood. While suggestions concerning possible points of contact with other—both Jewish and Christian—exegetical trends are raised, the peculiarities and the polemical overtones of the CT stance are duly emphasized. It is suggested that these peculiarities should be taken into consideration in the discussion on CT's provenance.